Modeling microplastic transport and residence time in a tide-dominated Amazonian estuary: A case study in Guajará Bay – Pará, Brazil - Matheus Pamplona Santiago; Thaís Angélica da Costa Borba; Marcio Machado Cintra; Marco Antônio Vieira Callado; Ana Hilza Barros Queiroz; Marcelo Rollnic (Journal of Marine Studies, 2026)
This case study presents the first numerical simulation of surface microplastic transport in the Amazon region, using a hydrodynamic model coupled with a water quality model in Delft3D software. This research investigated the transport of microplastics released by the Tamandaré River into Guajará Bay waters (using observational data to parameterize released microplastics), together with an analysis of hydrodynamic transport timescales (i.e., renewal rate, age of continental water, and residence time). The renewal rate is the time it takes for the waters of the open boundary to wash the initial waters of the domain; the age of continental water corresponds to the lifetime (in days) of a water parcel from its entry at the fluvial boundary to control points; and residence time indicates how long a water parcel remains within a semi-closed estuarine body into which it was released. These indicators were analyzed jointly, enabling an integrated understanding of microplastic transport dynamics. The results show that the decrease in river discharge during the dry season increased the residence time and age of continental water, while reducing the renewal rate, prolonging the persistence of microplastics in Guajará Bay. During the wet season, the opposite pattern occurred. Seasonally, the residence time of Tamandaré River waters in the Bay varied from 8 to 32 days, requiring approximately 36 to 72 days to leave the domain. Although positive tidal asymmetry and marginal vegetation are common factors for plastic accumulation in estuarine environments, this study demonstrated that the morphological configuration (i.e., the slope of the bank relative to the channel and the riverbank bathymetry) was decisive for the local dispersal pattern. Two areas of temporary sinks were identified in this urban estuarine system: on the right bank of Guajará Bay (BG1) and on the right bank of the mouth of the Guamá River (RG).